MAKNA SIMBOLIS PANTANGAN PADA WANITA HAMIL DI PEDESAAN BANYUMAS SYMBOLIC MEANING OF TABOOS ON PREGNANT IN THE VILLAGES OF BANYUMAS - Priyadi, Sugeng (Pembangunan Pedesaan, 2006)
Banyumas people have many taboos whether on elite people or in the villagers such as taboo on the pregnant. The taboos were categorized into taboo on food and taboo on behavior. The main objective of the pregnant in Banyumas was the safety of their baby and herself until the baby was born. The meaning of taboo basically was the control toward negative behavior, ethic deviation, and respect on the totemism symbol.